Acute effects of different types of oil consumption on endothelial function, oxidative stress status and vascular inflammation in healthy volunteers. - Tousoulis, D; Papageorgiou, N; Antoniades, C; Giolis, A; Bouras, G; Gounari, P; Stefanadi, E; Miliou, A; Psaltopoulou, T; Stefanadis, C (2010)
Consumption of different types of oil may have different effects on cardiovascular risk. The exact role of maize oil, cod liver oil, soya oil and extra virgin olive oil on endothelial function, oxidative stress and inflammation is unknown. We evaluated the effect of acute consumption of these types of oil on endothelial function, oxidative stress and inflammation in healthy adults. Thirty-seven healthy volunteers were randomised to receive an oral amount of each type of oil or water. Endothelial function was evaluated by gauge-strain plethysmography at baseline and 1, 2 and 3 h after consumption. Oxidative stress status was determined by total lipid peroxides (PEROX), while inflammatory process was estimated by measuring the soluble form of vascular adhesion molecule 1. Serum levels of the two previous markers were measured at baseline and 3 h after oil consumption. Reactive hyperaemia (RH) was significantly decreased after maize oil consumption compared with controls (P < 0.05). However, the consumption of cod liver oil and soya oil induced a significant improvement of RH after 1 h, compared with controls (P < 0.05). There was no significant effect of any type of oil consumption on endothelium-independent dilatation, total lipid PEROX and vascular adhesion molecule 1 serum levels. Consumption of maize oil leads to impaired endothelial function, while soya oil and cod liver oil slightly improve endothelial function. However, all types of oils did not affect inflammatory process and systemic oxidative stress, suggesting that their effect on endothelial function may not be mediated by free radicals bioavailability.